Acculturation Experiences of International Students from Sao Tome and Principe in China: A phenomenological study - Lyu, Ping; Sazali Yusoff (Journal of International Students, 2023)
While many studies are focused on international students from the main source countries in China, few studies have addressed how minority groups experience acculturation. Therefore, an interpretive phenomenology was used to explore the acculturation experiences of international students from Sao Tome and Principe (STP) studying in China. Semi-structured interviews were conducted with eight STP students, while analyzing the interview data using the Colaizzi method. Finally, the data yielded a total of four themes that were emerged as follows: 1. surprising explorers, 2. temporary mutes, 3. confused newcomers, and 4. elite pioneers. The findings provide insights into how the acculturation process is experienced and the strategies STP students in China followed toward it and are even consistent with existing theories and literature. International students from STP and other minority groups may benefit a lot from this study and enrich their experience of the acculturation process in a more targeted way.